(untitled) (Research, Society and Development, 2021)
Beet has attracted attention as a functional food with an important health-promoting effect. It presents in its composition important bioactive substances, highlighting betalains, ascorbic acid, carotenoids and phenolic acids. Ionic gelation encapsulation has been shown to be an effective technique in obtaining palatable and nutritious products masking unwanted flavors and preserving nutrients. Therefore, the objective of the present study was to obtain beet microcapsules by the process of ionic gelation and to verify the stability of bioactive compounds during refrigerated storage in different conservative solutions (standard, citric acid and ascorbic acid). From the beet extract, the ionic gelation process was carried out, obtaining the beet microcapsules, storing them for 28 days in airtight glass containers at 5 ± 1°C and with conservative solutions. The analyzes performed were, weight, size, color, soluble solids, moisture, ash, acidity, pH, vitamin C, carotenoids, betalains, phenolics and ABTS. The physical-chemical characteristics of the extract in relation to beet microcapsules, there was a significant reduction in soluble solids, betalain, antioxidant capacity, carotenoids and color parameter a*. Ascorbic acid, total phenols, ash, moisture and pH remained constant (5%). After 21 days of storage, an increase in the permeability of the alginate membrane was observed, causing greater migration between the compounds of the medium and the microcapsules. It is concluded that the ionic gelation process is a viable technology for the development of microcapsules of beet extract maintaining its nutritional characteristics, and the microcapsules stored in the solution with ascorbic acid had better results for bioactive compounds.